2006
DOI: 10.1080/13651820510037620
|View full text |Cite
|
Sign up to set email alerts
|

Biliary reconstruction using non‐penetrating, tissue everting clips versus conventional sewn biliary anastomosis in liver transplantation

Abstract: Biliary reconstruction can be performed clinically using NTEC as an alternative to conventional sewn biliary anastomoses with good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition to RYHJ and either end‐to‐end or side‐to‐side CDC, other options of biliary anastomosis have been explored. Thomas et al showed that nonpenetrating, tissue‐everting clips for end‐to‐end CDC have rates of biliary complications equal to that of conventional hand‐sewn anastomoses 12. In addition, there are experimental reports indicating the use of fibrin glue for end‐to‐end CDC in dogs, which showed biliary complication rates of 30% 13…”
Section: Discussionmentioning
confidence: 99%
“…In addition to RYHJ and either end‐to‐end or side‐to‐side CDC, other options of biliary anastomosis have been explored. Thomas et al showed that nonpenetrating, tissue‐everting clips for end‐to‐end CDC have rates of biliary complications equal to that of conventional hand‐sewn anastomoses 12. In addition, there are experimental reports indicating the use of fibrin glue for end‐to‐end CDC in dogs, which showed biliary complication rates of 30% 13…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective randomized trial comparing interrupted and continuous suture in CDC, showed no differences between both suture types with respect to the incidence of leaks and strictures (166). A new technique of end‐to‐end CDC using vascular staples was proposed recently by Thomas (167). In this study tissue everting clips were compared with a conventional handsewn technique showing no differences in biliary complications between both techniques.…”
Section: Biliary Anastomosismentioning
confidence: 99%